Impact of Biochar on Growth, Physiology and Antioxidant Activity of Common Bean Subjected to Salinity Stress - Kul, Raziye; Ekinci, Melek; Turan, Metin; Yildirim, Ertan (Global Journal Of Botanical Science, 2021)
A pot study was carried out to evaluate the impacts of biochar applications on the growth, physiological properties, and antioxidant enzyme activity of common beans under salinity stress. The experiment was conducted in a completely randomized design with two salinity levels of NaCl [S0 (control, 0 mM NaCl) and S1 (100 mM NaCl)] and three biochar levels [BC-0 (control, non-biochar), BC-1 (2.5%) and BC-2 (5 %)]. Results of the study revealed that plant growth, relative leaf water content (LRWC), and chlorophyll reading value (CRV) of common bean decreased significantly, while malondialdehyde (MDA), hydrogen peroxide (H2O2), proline, and sucrose content increased significantly with salinity stress. Biochar applications mitigated the negative impact of salinity stress on plant growth and physiological characteristics of common beans. The salinity tolerance due to biochar applications could be associated with a significant reduction of antioxidant activity, MDA and H2O2, and an increase of LRWC and chlorophyll content. Therefore, it can be concluded that biochar could be used to reduce the negative impacts of salinity stress in common bean.